Eliciting and Annotating Emotion in Virtual Spaces - Xylakis, Emmanouil; Najm, Ali; Michael-Grigoriou, Despina; Liapis, Antonios; Yannakakis, Georgios N. (My University, 2023)
We propose an online methodology where moment-to-moment affect annotations are gathered while exploring and visually interacting with virtual environments. For this task we developed an application to support this methodology, targeting both a VR and a desktop experience, and conducted a study to evaluate these two media of display. Results show that in terms of usability, both experiences were perceived equally positive. Presence was rated significantly higher for the VR experience, while participant ratings indicated a tendency for medium distraction during the annotation process. Additionally, effects between the architectural design elements were identified with perceived pleasure. The strengths and limitations of the proposed approach are highlighted to ground further work in gathering affect data in immersive and interactive media within the context of architectural appraisal.
Keywords: Affective Computing; Architectural Design; Human Computer Interaction; Online Annotation; Perceived Pleasure; Virtual Reality